AUTOFIGURACIONES: DE LA FICCIÓN AL PACTO DE NO FICCIÓN - POZUELO YVANCOS, José Mª (Signa: Revista de la Asociación Española de Semiótica, 2022)
Partiendo de una concepción del género literario como resultado de casillas vacías que la creación literaria impone a la teoría como desafío, este estudio intenta avanzar de modo diferente al de la conocida como Autoficción, precisando mi propuesta avanzada en 2010 sobre Figuraciones del yo. Entre las que ahora denomino Autofiguraciones enumero algunas muy presentes en la literatura de hoy en las que, al igual que ocurre con los relatos de la Shoah de Primo Levi, desarrollan un pathos por el cual el autor compromete experiencias que piden ser leídas como no ficcionales para alcanzar una lectura feliz. El estudio se refiere a obras recientes de diferentes autores que han partido de las Grief Memoir o libros de duelo (por la muerte de padre, madre o hijos) que sobrepasan con mucho cualquier ambigüedad respecto al dolor originario. La segunda parte del estudio desarrolla la tesis de que no toda invención imaginaria pide ser leída como ficción, y que incluso en pactos autobiográficos que nacen deconstructivos (como los de Barthes o Roth) hay mecanismos de referencia, como las fotos, que quieren evadirse de la cárcel del lenguaje. Tanto la multiplicación de detalles sensoriales como un especial juego con el tiempo de la memoria, ahondan en la misma dirección. A partir del concepto bajtiniano de cronotopo externo preciso que toda decisión sobre Ficción/No ficción en las autofiguraciones debe dirimirse de modo pragmático. Avanzo que en obras como las analizadas hay pactos de no ficción que permiten, al contrario que las ficcionales, que puedan formularse desde el que llamo tu autobiográfico reproches posibles sobre olvidos, silencios o mendacidades. ABSTRACT: Beginning with a conception of the literary genre as a result of empty boxes that literary creation imposes on theory as a challenge, this study aims to advance in a different way from the one known as Autofiction, specifying my prior proposal in 2010 on Figuraciones del yo. Among the ones I now call Autofigurations, I list some very present in today’s literature in which, as it happens with the stories of the Shoah by Primo Levi, they develop a pathos by which the author compromises experiences that ask to be read as non-fictional in order to achieve a happy reading. This study refers to recent works by different authors who have started from the Grief Memoirs or books of mourning (for the death of a father, mother or children) that go far beyond any ambiguity regarding the original pain. The second part of the study develops the thesis that not every imaginary invention asks to be read as fiction, and that even in autobiographical pacts that are born deconstructive (like those of Barthes or Roth) there are referential mechanisms, like photos, that want to escape from the prison of language. Both the multiplication of sensory details and a special game with the time of memory go in the same direction. From Bakhtin’s concept of external chronotope, it is clear that any decision on fiction/non-fiction in self-portraits must be made pragmatically. I warn that in works such as those analysed there are non-fiction pacts that allow, unlike fictional works, possible reproaches about forgetfulness, silence or mendacity to be formulated from what I call the autobiographical-you. Abstract: Beginning with a conception of literary genre as the result of empty boxes that literary creation imposes on theory as a challenge, this study attempts to move forward in a different way to that of what is known as Autofiction. Among what I now call Autofigurations, I list some very present in current literature which, starting from the Grief Memoir, develop a pathos on which they ask to be read as non-fictional. The second part of the study develops this thesis that not every imaginary invention asks to be read as fiction, pointing out mechanisms of reference, such as photographs, that want to escape from the prison of language. Based on Bakhtin’s concept of the external chronotope, it is clear that any decision on fiction/non-fiction in self-figurations must be made pragmatically. In works such as those analysed, there are non-fictional pacts which, unlike fictional ones, allow us to formulate, from what I call the autobiographical-you, possible objections to forgetfulness, silences or mendacities.